SENSOR ELETROQUÍMICO FABRICADO VIA IMPRESSÃO 3D PARA QUANTIFICAÇÃO DE MISTURAS ETANOL/ÁGUA VIA ESPECTROSCOPIA DE IMPEDÂNCIA ELETROQUÍMICA. - PABLO DE ANDRADE PAIXÃO (2024)
We developed a miniaturized and low-cost electrochemical 3D-printed system for rapid and accurate quantification of ethanol content in ethanol fuel using electrochemical impedance spectroscopy (EIS). The monolithic design of the system incorporates insulating thermoplastic electrode separators, with only the cover being mobile, allowing for easy assembly and handling. The portable device, measuring approximately 26 x 24 mm, has a maximum capacity of 1 mL, making it suitable for lab-on-a-chip and portable analysis. By utilizing the dielectric constant of ethanol and ethanol fuel mixtures with water, the miniaturized EIS-cell quantifies ethanol content effectively. To validate its performance, we compared measurements from four gas stations with a digital densimeter, and the values obtained from our system matched perfectly. Our miniaturized and low-cost electrochemical 3D-printed device can be printed and assembled in under 2 h, offering a cost-effective solution for fast and precise ethanol quantification. Its versatility, affordability, and compatibility with portable analysis platforms make it highly applicable in various industries, including fuel quality control and on-site analysis in remote locations.